Bruxism an issue between the myths and facts = Bruxismo, un problema entre los mitos y los hechos - Cervantes Chavarría, Andrés R 1986-
Is our goal in this paper to discuss the current concepts about bruxism, a topic that has been a matter of discussion on the dental field for many years. Recent International efforts have been made to challenge bruxism old definitions; this has derivate to a consensus and an actual new concept that defines bruxism as a behavior instead of a disorder. As a behavior, it is explained in this review how it can have negative health consequences, can be innocuous and how new research support that bruxism can even be a protective factor. Different etiological factors are reviewed in this paper as well the influence of external and internal mechanism related to medications, emotional stress, systemic factors, and potential pharmacological pathways. Moreover, it is briefly summarized the role of oral appliances on sleep bruxism. Finally, clinical considerations and recommendation for the dental professional regarding sings that should be notice during the exam are part of this overview.